Quantitative analysis of lactic acid oligomers from dimer to 15mer in poly(D, L-lactide) (PDLLA) polymers. Issue 2 (17th February 2021) - Hu, Xiaoyi; Kamberi, Marika; Xu, Xinmin
Abstract: Poly(D, L-lactide) (PDLLA) polymer is widely used in biomedical applications. To control the degradation of PDLLA, as well as to ensure effective quality control of the polymer raw material, it is essential to have analytical methods capable of analyzing the PDLLA oligomer species content quantitatively. In this study, liquid chromatography-mass spectrometry (LC-MS) based analytical methods were developed to quantitate oligomer species from dimer to 15mer (total of 14 analytes) in the PDLLA polymer resin. Negative electrospray ionization was employed as the LC-MS interface. For the lactic acid dimer and trimer analysis, a SIELC Primesep SB column was used for high performance liquid chromatography (HPLC) separation and selected reaction monitoring (SRM) was used as the acquisition mode. For other lactic acid oligomer (4mer to 15mer) analysis, a Phenomenex Synergi™ 4 µm Polar-RP column was used, and selected ion monitoring (SIM) was used as the acquisition mode. Both columns demonstrated good tolerability for samples with high polymer content which is critical for method development. Analytical parameters such as calibration, correlation, accuracy, and precision were evaluated. Quadratic functions best described the correlation between response and concentration for each oligomer analyte. Excellent accuracy and precision were demonstrated with both methods. The methods developed in this study can be used to evaluate the impact of manufacturing process on polymers and can also be a good reference for oligomer analysis method development of similar polymers.